Relationships between Environmental Factors and a History of Falling with the Fear of Falling (FOF) among Elderly in the Community - Ulfiana, Elida; Makhfudli, Makhfudli; Hadisuyatmana, Setho; Priambodo, Rian; Chotimah, Kusnul (International Journal of Psychosocial Rehabilitation, 2020)
Falls among community-dwelling older people are a major issue worldwide. Falls are one of the effects of the aging process. Increased risk of falls in the elderly is caused by intrinsic and extrinsic factors and occurs due to multifactorial issues. The purpose of this study was to analyze the relationship between the environment and history of falling towards the fear of falling among elderly in the community. This study used a descriptive-analytic cross-sectional design. Sampling was carried out using a cluster random sampling technique with a sample of 210 elderly in Surabaya and Lamongan district. The respondent were recruited through Posyandu Programs. The independent variables were environmental factors and history of falling, while the dependent variable was the fear of falling among the elderly. The research instrument used was a home fall prevention checklist for older adults, Open questions on the history of falling among the elderly, and the Falls Efficacy scale (FES-I) were used to measure the fear of falling. Analysis was carried out using the Chi Square test with degrees α = 0.05. Results: statistical test results showed a relationship of environmental factor with a fear of falling (p=0.001) and there was a relationship of history of falling with a fear of falling (p=0.001). A risky home safety environment and a history of falling will cause the risk of fear of falling among the elderly.